Clinical Analysis of Pediatric Systemic Juvenile Xanthogranulomas: A Retrospective Single-Center Study - Lian, Hongyun; Wei, Ang; He, Lejian; Yang, Ying; Ma, Honghao; Zhang, Liping; Guan, Yitong; Zhang, Qing; Wang, Dong; Li, Zhigang; Zhang, Rui; Wang, Tianyou (Frontiers in Pediatrics, 2021)
Objective To investigate the clinical characteristics, treatment, and prognosis of children with systemic juvenile xanthogranuloma (JXG). Methods Clinical data of children with JXG who were hospitalized in Beijing Children’s Hospital, Capital Medical University, from January 2012 to December 2019 were retrospectively analyzed, including clinical manifestations, laboratory determinations, treatment, and prognosis of the children. Patients were treated with vindesine + prednisone as the first-line treatment and cytarabine + vindesine + dexamethasone +/- cladribine as the second-line treatment. Results Ten patients, including 8 males and 2 females, with a median of onset age of 1.95 (0.80-7.30) years, exhibited multi-system dysfunction. The median age of diagnosis was 2.45 (1.30-12.10) years. The most common location of extracutaneous lesions was the central nervous system (6 cases), followed by the lung (5 cases) and bone (4 cases). Nine patients underwent first-line chemotherapy, and 6 patients underwent second-line chemotherapy, including 5 patients with poorly controlled disease after first-line treatment. The median observation time was 29 (3-115) months. Nine patients survived, whereas one patient died of respiratory failure caused by pulmonary infection. At the end of follow-up, 7 patients were in active disease (AD)/regression state (AD-better), and 2 patients were in an AD/stable state (AD-stable). Three patients had permanent sequelae, mainly central diabetes insipidus. The rates of response to the first-line treatment and the second-line treatment were 40.0% and 66.7% respectively. Conclusion The chemotherapy protocol for Langerhans cell histiocytosis (LCH) may be effective for patients with systemic JXG. Central nervous system involvement may not impact overall survival, but serious permanent sequelae may occur.